Expression and function of drug transporters in an in vitro model of the mammary epithelial barrier (BME-UV) - Al-Bataineh, Mohammad M. (Kansas State University, 2010)
Milk composition has a dynamic nature, and the composition varies with stage of lactation, age, breed, nutrition and health status of the udder. The changes in milk composition seem to match the changes in the expression of membrane proteins in secretory mammary epithelial cells that are needed for the movement of molecules from blood to milk and vice versa (Nouws and Ziv, 1982). Thus, an understanding of transporter expression, function and regulation in mammary epithelial cells can provide insight into mammary gland function and regulation. The goal of this project was to elucidate (molecularly and functionally) the role of drug transporters in the barrier function of an epithelial monolayer cultured from an immortalized bovine mammary epithelial cell line (BME-UV). To characterize the regulation (expression and function) of these drug transporters in BME-UV cells after exposure to cytokine TNF-α for selected periods of time. Representative members of drug transporters of the SLC (OCT and OAT) and ABC (P-glycoprotein) superfamilies were chosen for this project. In the first study, the involvement of a carrier-mediated transport system in the passage of organic cation (TEA) and anion (EsS) compounds was elucidated across the BME-UV monolayer. In the second study, molecular and functional expression of bOAT isoforms in BME-UV cells were studied. The final study characterized the effects of cytokine TNF-α on the expression and function of P-glycoprotein, an efflux pump, in BME-UV cells. Cytokine TNF-α exposure induced the expression of ABCB1 mRNA and increased P-glycoprotein production in BME-UV cells, resulting in a greater efflux of digoxin, a known P-glycoprotein substrate, back into the apical fluid. The expression, function, and regulation of these transporters in the mammary gland has important implications for understanding the barrier function of the mammary epithelium and, in more specific, for characterizing the role of these transporters in the accumulation and/or removal of specific substrates from milk and/or plasma. Moreover, this study provides an in vitro cell culture model of mammary epithelium to characterize mammary epithelial cell function during inflammation.
Keywords: Mammary epithelial cell; Drug transporters; Pharmacokinetic; Tumor necrosis factor-alpha; Biology, Cell (0379); Biology, Veterinary Science (0778); Health Sciences, Pharmacology (0419)